Iatrogenic injury and regeneration of the facial nerve after parotid gland tumour surgery: a pilot study with clinical and neurophysiological assessment (Journal of Medical Science, 2020)
Introduction. Benign tumour surgery of the parotid gland may cause iatrogenic injury of the facial nerve, with results of postoperative treatment depending on the type of injury. The study aimed to clarify the mechanism of facial nerve injury after benign tumour surgery of parotid gland. Materials and Methods. The effectiveness was verified preoperatively and 1, 3, 6 and 17 months postoperatively. House-Brackmann scales, electroneurography, blink reflex study and needle electromyography were performed. Pharmacological treatment (Galantamine, Cocarboxylase, Dexamethasone, Triamcinolone) and supervised physiotherapeutic procedures (Facial-Oral-Tract-Therapy, Proprioceptive neuromuscular facilitation) were applied for six months. Results. Tumour removal led to the total paralysis of the left facial nerve, IV, III and III House-Brackmann grades were ascertained at the subsequent 3rd–5th periods of observation. In postoperative studies, electroneurography results showed full functional recovery of the frontal branch and incomplete regeneration in the marginal mandibular branch. Blink reflex examination showed proper parameters of evoked potentials only during preoperative and the last observation period. Residual voluntary activity of the frontal muscle and weak voluntary activity of orbicularis oris muscle were recorded in the needle electromyography examination. Contracture of mimic muscles at rest and improvement of their voluntary activity on the left side was observed six months after surgery compared to the early period of observation. Conclusion. Consecutive studies showed the predominant axonal type of injury in the marginal mandibular branch and neuropraxia effect of the facial nerve, allowing the creation of a rehabilitation programme optimal for the functional recovery of the nerve.